The Price of Oil - Will it Start Rising Again? - Fournier, Jean-Marc (OECD Economics Department Working Papers, 2013)
Following a sharp drop amidst the global economic crisis and a subsequent recovery, the spot price of crude oil has been broadly stable for the past couple of years. This paper discusses the factors that drive oil demand and supply and, hence, the price of the resource. A set of oil demand equations is estimated for OECD and non-OECD countries, which is then combined with assumptions about the behaviour of supply to analyse the impact of a range of macroeconomic and policy scenarios on the future oil price path. The scenario analysis suggests that a return of world growth to slightly below pre-crisis rates would be consistent with an increase in the price of Brent crude to far above early-2012 levels by 2020. This increase would be mostly driven by higher demand from non-OECD economies - in particular China and India. The expected rise in the oil price is unlikely to be smooth. Sudden changes in the supply or demand of oil can have very large effects on the price in the short run